2010
DOI: 10.1007/s11695-010-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Neck Circumference on Respiratory Endurance and Muscle Strength in the Morbidly Obese

Abstract: Although adiposity patterns did not affect inspiratory muscle strength, neck adiposity was associated lower respiratory muscle endurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…There was a statistically significant difference in MPT values for the vowels [a], [i], and [u] before and after bariatric surgery (Table 1), which corroborates with the findings of other authors [7][8][9]15] who found a reduction in this parameter in individuals with obesity. This result can be explained by the presence of fat in the neck in obese individuals, which predisposes the increase in type II muscle fibers in the dilator muscles of the upper airways, causing lower respiratory muscle strength [17] and difficulty in mobilizing the airflow to the same degree as in non-obese individuals. This configuration may explain the imbalance between the myoelastic and aerodynamic forces of the larynx and result in reduced MPT [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a statistically significant difference in MPT values for the vowels [a], [i], and [u] before and after bariatric surgery (Table 1), which corroborates with the findings of other authors [7][8][9]15] who found a reduction in this parameter in individuals with obesity. This result can be explained by the presence of fat in the neck in obese individuals, which predisposes the increase in type II muscle fibers in the dilator muscles of the upper airways, causing lower respiratory muscle strength [17] and difficulty in mobilizing the airflow to the same degree as in non-obese individuals. This configuration may explain the imbalance between the myoelastic and aerodynamic forces of the larynx and result in reduced MPT [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the measurement of NC can be used to define obesity and that excess fat and muscle can overwhelm the respiratory system [17]. It is worthy of note that the accumulation of fat in the neck may cause stress on the extrinsic muscles of the larynx, which are secondarily responsible for voice frequency [16], by restricting the extent of laryngeal movement and consequently reduce this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…The circumferences were measured in centimeters using a non-elastic tape measure. Neck circumference was measured at the cricoid cartilage 16 ; waist circumference was measured at the midpoint between the margin of the last rib and the upper margin of the iliac crest; hip circumference was measured at the greater trochanter of femur 17 ; and with the measures of waist circumference and hip circumference, the waist/hip ratio was obtained.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…The correlation between body shape and fundamental frequency seems plausible in some cases, considering the larynx is the hormonal target 4 ,56, 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 . However, studies show that weight and body shape of male and female adults are negatively correlated with fundamental frequency 7 .…”
Section: Introductionmentioning
confidence: 99%